Preoperative Management of Diabetic Patients Undergoing Abdominal Surgery - Muhammad Zeb, Jawadalam Khattak, Shumaila Sikander, Mirwais, Maryam Munir, Muhammad Asim Jamal, Niaz Ali Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: The management of diabetic patients undergoing abdominal surgery presents a multifaceted challenge that demands a comprehensive and tailored approach to ensure optimal perioperative outcomes Objectives: The basic aim of the study is to find the preoperative management of diabetic patients undergoing abdominal surgery Material and methods: A retrospective analysis was conducted, utilizing medical records from a cohort of 200 diabetic patients who had undergone various abdominal surgical procedures at Khyber Teaching Hospital Peshawar between August 2018 to March 2019. Ethical approval was obtained from the Institutional Review Board (IRB) prior to the commencement of data collection.Electronic medical records were meticulously reviewed to gather comprehensive patient information. Relevant demographic data, including age, gender, and body mass index (BMI), were documented. Preoperative glycemic status, measured through fasting blood glucose levels, HbA1c levels, and medication regimens, were recorded. Patient comorbidities, particularly cardiovascular conditions, were identified, and details of preoperative cardiovascular risk assessments were documented. Practical Implication: The prevalence of postoperative complications emphasizes the need for comprehensive management. These findings underscore the significance of holistic approaches to ensure safer surgeries and improved patient well-being. Conclusion: It is concluded that glycemic control, collaborative cardiovascular risk assessment, nutritional optimization, and patient education play pivotal roles in enhancing surgical outcomes. The prevalence of postoperative complications emphasizes the need for comprehensive management. Keywords: Diabetic, abdominal surgery, postoperative complications, nutritional optimization, cardiovascular risk, Nutritional Optimization